PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS KOMPETENSI BERORIENTASI PRODUKSI PADA MATA KULIAH DASAR FOTOGRAFI MENGGUNAKAN APLIKASI SIGIL - Zaudah Cyly; Sulistianingsih AS; Yogo Dwi Prasetyo; Yudho Setyo Nugroho (Steam Engineering, 2023)
Learning activities in the Fundamentals of Photography course which have been running so far have experienced several obstacles including the absence of teaching materials specifically designed to be effective, efficient, and attractive in learning. Some basic photography material should be carried out in practice, but in reality, it must be delivered in theory given the limited time and learning resources and the low learning outcomes and results of student creativity in the field of photography which does not meet the standards for completeness assessment. To overcome these problems, competence-based and production-oriented digital teaching materials are developed which are valid and suitable for use in learning activities as well as for student self-study. This research is a type of development research using the Dick and Carey model with the final product being a digital textbook developed with the help of the Sigil application. The approach used is a competency-based and production-oriented learning approach. Before testing D3 Multimedia Computer STT STIKMA Internasional student, validation was carried out on material experts and media experts, which were then corrected according to the expert's assessment. Data from the trial results during implementation activities in learning were analyzed using descriptive statistics and questionnaire calculations from respondents using criteria from the Likert scale. Indicators of success and feasibility of measuring digital teaching materials are assessed from the feasibility of content, presentation of content, language, graphics, and assessment at the end of learning activities. The results of validation by experts and trials on students show that basic digital photography teaching materials have the feasibility and validity to be used as a supplement in facilitating student learning and practicum learning while taking photography basics courses.